A comparative approach to affect and cooperation. (December 2019) - Massen, Jorg J.M.; Behrens, Friederike; Martin, Jordan S.; Stocker, Martina; Brosnan, Sarah F.
Highlights: Theoretical work assumes a mediating role for emotions in cooperative decision-making. Recent developments have enabled the study of animal affect. A proper comparative framework allows for investigation of the actual role of affect in cooperative decision-making. Abstract: A central premise of the science of comparative affect is that we can best learn about the causes and consequences of affect by comparing affective phenomena across a variety of species, including humans. We take as a given that affect is widely shared across animals, but a key challenge is to accurately represent each species' affective experience. A common approach in the comparative study of behavior and cognition is to develop standardized experimental paradigms that can be used across species, with the assumption that if the same task is being used, we can directly compare behavioral responses. This experimental approach rests on two underlying assumptions: first, that different species' perception of and affective response to these paradigms are the same; and second, that behavioral and physiological (including endocrine and neural) responses to these paradigms are homologous; if either of these assumptions is not true, then the comparison becomes much less straightforward. Our goal in the present paper is to summarize the dominant paradigms that have been used for such comparative research, with a particular focus on paradigms common in the cooperation literature, and to critically discuss dominant assumptions about what affective states these tasks can or should measure. We then consider the advantages and drawbacks of this experimental method, and consider alternatives that may improve our understanding. We hope that this will help scholars recognize and avoid pitfalls inherent in studying affect, and stimulate them to create novel, ecologically relevant paradigms for examining affect across the animal kingdom.